1994
DOI: 10.1017/s001667230003250x
|View full text |Cite
|
Sign up to set email alerts
|

The inheritance of female mating behaviour in the seaweed fly,Coelopa frigida

Abstract: In order to understand the evolution of female mate preferences it is important to determine whether the genes for the preference and those for the preferred character are linked. It has previously been shown that female preference in the seaweed fly, Coelopa frigida, varies with the a/? inversion system on chromosome I. This inversion system is known to genetically determine, at least in part, the male preferred character, large size. This study was undertaken to determine whether the genes determining mate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Houde has shown that the female preference function of guppies for orange tail coloration in males varies between two populations; one population shows a strong, possibly stabilizing, pattern (30), whereas the other consists of nonchoosy females, resulting in a flat preference function (31). In an elegant series of experiments Gilburn and Day (32,33) have used cubic spline analysis to examine female preferences of the dipteran Coelopa frigida by analyzing acceptance rates during pairing in the laboratory versus male size, for individuals of different genotypes. The preference function differs both between populations and between females of different genotypes (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Houde has shown that the female preference function of guppies for orange tail coloration in males varies between two populations; one population shows a strong, possibly stabilizing, pattern (30), whereas the other consists of nonchoosy females, resulting in a flat preference function (31). In an elegant series of experiments Gilburn and Day (32,33) have used cubic spline analysis to examine female preferences of the dipteran Coelopa frigida by analyzing acceptance rates during pairing in the laboratory versus male size, for individuals of different genotypes. The preference function differs both between populations and between females of different genotypes (32).…”
Section: Discussionmentioning
confidence: 99%
“…The preference function differs both between populations and between females of different genotypes (32). It can also differ for environmental reasons, and was unstable in the laboratory (33).…”
Section: Discussionmentioning
confidence: 99%
“…Coelopa frigida is an established model organism for research into sexual selection and sexual conßict (Butlin et al 1982;Gilburn and Day 1994, 1996Day et al 1996;Dunn et al 2002;Gilburn 2005, 2006;Edward and Gilburn 2007). The mating behavior of the other common British seaweed ßy, Coelopa pilipes, has also been studied (Crean et al 2000, Dunn et al 2002, Edward and Gilburn 2007, albeit to a lesser extent.…”
mentioning
confidence: 99%
“…Sexual displays are absent and males simply mount other flies and then attempt to copulate with females (Day et al 1990). Females, however, are more amenable to copulation (struggling less) when they are mounted by large males (quantified by measuring wing size) (Shuker and Day 2002) and when females carry a specific chromosomal inversion that confers large size (Gilburn and Day 1994;Gilburn and Day 1999), which also confers a preference for large males (Butlin et al 1982). Although wing displays have yet to be documented in any seaweed flies, other dipterans have been shown to use their wings in display behaviour (Alonso-Pimentel et al 2000;Briceno and Eberhard 2000;Lasbleiz et al 2006).…”
Section: Introductionmentioning
confidence: 99%